2007
DOI: 10.1271/bbb.60380
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Effects of Odorless Garlic Powder Bothin Vitroandin Vivo

Abstract: Antithrombotic activities of odorless garlic powder were demonstrated in blood fibrinolytic and coagulation systems. Though the odorless garlic preparation did not influence tissue-type plasminogen activator (t-PA) or its inhibitor secretions from human umbilical vein endothelial cells, it enhanced plasmin generation by t-PA on fibrin film and in chromogenic assays by 1.8-fold and 8.7-fold respectively. The coagulation system was considerably reduced after the administration of the garlic in a rat in situ loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 18 publications
0
38
1
4
Order By: Relevance
“…Garlic is widely accepted as a herb that through dietary intake can improve human health (61). Epidemiological studies have shown that a daily intake of garlic lowers the risk of certain cancers (25,63), and several studies have documented an antithrombotic and lipid-lowering cardiovascular effect of some of the constituents in garlic (27).…”
mentioning
confidence: 99%
“…Garlic is widely accepted as a herb that through dietary intake can improve human health (61). Epidemiological studies have shown that a daily intake of garlic lowers the risk of certain cancers (25,63), and several studies have documented an antithrombotic and lipid-lowering cardiovascular effect of some of the constituents in garlic (27).…”
mentioning
confidence: 99%
“…Garlic constituents can reduce fibrin formation and also help reduce the fibrin existing in the blood more efficiently than aspirin 42 .…”
Section: Thinning Of Bloodmentioning
confidence: 99%
“…Otro estudio con ajo en polvo ha demostrado que este favorece la actividad fibrinolítica además de suprimir el sistema de coagulación previniendo así la formación de trombos (20). Estos resultados se han corroborado en otro trabajo, en el cual se demuestra que el extracto alcohólico de ajo es un potente inhibidor de la agregación plaquetaria (21).…”
Section: Efecto Sobre La Tensión Arterial Y Endotelio Vascularunclassified